The Morphometric Analysis of the Human Thyroid of the Endemic Region of Ukraine - Mota, Oksana; Halyuk, Ulyana; Pokotylo, Petro; Lohash, Maxim; Zboina, Bożena; Ślusarska, Barbara; Król, Halina; Czerwińska Pawluk, Iwona; Zukow, Walery (Journal of Education, Health and Sport, 2020)
Introduction. Since the thyroid gland (TG), like the rest of the human body, is characterised by wide variety in shape and size, the evaluation of its linear and volumetric parameters by ultrasound images is one of the most important and objective ways of quantitative characteristics of the organ. There are scarce studies into TG morphometry by ultrasound in the Precarpathian region, which is one of the oldest endemic places in Europe. Objective. The aim of the current research study is to conduct the morphometric analysis of TG in adolescents of different sex and constitution who are indigenous inhabitants of the Precarpathian region Materials and methods. Therefore, the morphometric analysis of TG linear and morphometric parameters has been conducted in 179 adolescents inhabiting the territory. Ultrasonography has been carried out in Lviv Regional Infectious Clinical Hospital by means of “CHISON” sonograph. Three longitudinal and three anteroposterior dimensions of TG right and left lobes at different levels were measured based on the sonograms taken UDC: 611. 641 ̶ 018.1:6at the angle of 20 - 30° to the median plane. The volume of each TG lateral lobe was measured by the following formula: AxBxCx0.52, where A is the lobe length, B is the lobe width, C is the lobe thickness, and 0.52 is the coefficient of allowance. Results. The ratio between the linear parameters of the lobes has been revealed to be determined rather by constitutional than by sex peculiarities of those under study. It is statistically probable that longitudinal dimensions of both lobes in dolichomorphic people of both sexes exceed the analogous ones in mesomorphs and brachymorphs of both sexes. TG lobes in brachymorphs, in particular, are wider compared with those in both mesomorphs and dolichomorphs, irrespective of sex. The analysis of TG volumetric parameters in different body types of both sexes has indicated that TG volume in brachymorphs dominates in volume over mesomorphs and dolichomorphs, irrespective of sex. Moreover, the volume of the right lobe is larger than the volume of the left one by 0.5 -1.0 cm3 in all of the body types of both sexes. The difference is especially marked in males of the brachymorphic body type. Although there is no statistically probable difference in male and female TG volumes of mesomorphs and dolichomorphs. TG volumes in male brachymorphs are markedly larger than in female ones. As for volume variations they are quite extensive from a minimal male TG volume of 4.85 cm3 to a maximal one of 17.52 cm3, and from a minimal female TG volume of 3.09 cm3 to a maximal one of 14.51 cm3. Conclusions. Thuse the results of TG morphometry by ultrasound demonstrate that there is a direct correlation between TG linear, volumetric parameters and sex or body types, which should be taken into consideration while making a diagnosis in order to avoid incorrect positive diagnoses of TG hypo- or hyperplasia.